Distributed tracking control of second-order multi-agent systems under measurement noises - Liu, Xueliang (2015)
This paper considers a leader-following tracking control problem for second-order multiagent systems (MASs) under measurement noises and directed communication channels. It is assumed that each follower-agent can measure the relative positions and velocities of its neighbors in a noisy environment. Based on a novel velocity decomposition technique, a neighbor-based control law is designed to realize local control strategies for these continuous-time agents. It is shown that the proposed consensus protocol can guarantee that all the follower-agents track the active leader. In addition, this result is extended to a more general case with switching topologies. Finally, a numerical example is given for illustration.